Diagnostic utility of exome sequencing in the evaluation of neuromuscular disorders. (February 2018) - Haskell, Gloria T.; Adams, Michael C.; Fan, Zheng; Amin, Krunal; Guzman Badillo, Roberto J.; Zhou, Linran; Bizon, Christopher; Chahin, Nizar; Greenwood, Robert S.; Milko, Laura V.; Shiloh-Malawsky, Yael; Crooks, Kristy R.; et al.
Abstract : Objective: To evaluate the diagnostic yield and workflow of genome-scale sequencing in patients with neuromuscular disorders (NMDs). Methods: We performed exome sequencing in 93 undiagnosed patients with various NMDs for whom a molecular diagnosis was not yet established. Variants on both targeted and broad diagnostic gene lists were identified. Prior diagnostic tests were extracted from the patient's medical record to evaluate the use of exome sequencing in the context of their prior diagnostic workup. Results: The overall diagnostic yield of exome sequencing in our cohort was 12.9%, with one or more pathogenic or likely pathogenic variants identified in a causative gene associated with the patient's disorder. Targeted gene lists had the same diagnostic yield as a broad NMD gene list in patients with clear neuropathy or myopathy phenotypes, but evaluation of a broader set of disease genes was needed for patients with complex NMD phenotypes. Most patients with NMD had undergone prior testing, but only 10/16 (63%) of these procedures, such as muscle biopsy, were informative in pointing to a final molecular diagnosis. Conclusions: Genome-scale sequencing or analysis of a panel of relevant genes used early in the evaluation of patients with NMDs can provide or clarify a diagnosis and minimize invasive testing in many cases.